2008
DOI: 10.1073/pnas.0711716105
|View full text |Cite
|
Sign up to set email alerts
|

Molecular conformation and dynamics of the Y145Stop variant of human prion protein in amyloid fibrils

Abstract: A C-terminally truncated Y145Stop variant of the human prion protein (huPrP23-144) is associated with a hereditary amyloid disease known as PrP cerebral amyloid angiopathy. Previous studies have shown that recombinant huPrP23-144 can be efficiently converted in vitro to the fibrillar amyloid state, and that residues 138 and 139 play a critical role in the amyloidogenic properties of this protein. Here, we have used magic-angle spinning solid-state NMR spectroscopy to provide high-resolution insight into the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

24
298
3
4

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 182 publications
(330 citation statements)
references
References 53 publications
24
298
3
4
Order By: Relevance
“…24,25 Instead, a variety of studies have investigated the structure of amyloid fibrils produced in vitro from recombinant PrP. [26][27][28][29][30][31][32][33][34][35] Hereditary prion diseases include C-terminally truncated variants of the PrP, Y145X, Q160X, Y226X, and Q227X. Previously, we showed that the b-sheet content is highly similar in amyloid fibrils of the Y145X and Q160X stop mutants of human PrP.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…24,25 Instead, a variety of studies have investigated the structure of amyloid fibrils produced in vitro from recombinant PrP. [26][27][28][29][30][31][32][33][34][35] Hereditary prion diseases include C-terminally truncated variants of the PrP, Y145X, Q160X, Y226X, and Q227X. Previously, we showed that the b-sheet content is highly similar in amyloid fibrils of the Y145X and Q160X stop mutants of human PrP.…”
Section: Resultsmentioning
confidence: 99%
“…36 In addition, solid-state NMR spectroscopy demonstrated that residues 112-140 assume extended b-sheet conformation in a parallel, in register alignment in amyloid fibrils of the Y145X stop mutant. [29][30][31] We subjected the solid-state NMR chemical shifts reported by Helmus et al 29 for amyloid fibrils of the Y145X prion stop mutant to the adapted CSRosetta protocol. 17 Calculations were performed on five identical segments that were connected by 16-residue glycine-serine linkers.…”
Section: Resultsmentioning
confidence: 99%
“…Amyloid fibrils contain a rigid core, where dipolar-based experiments transfer polarization with high effi- ciency, and mobile regions, where polarization transfer is inefficient in dipolar-based experiments (34,54). Thus, the signal intensities report qualitatively on rigidity.…”
Section: A30p As Fibrillates More Slowly Than Wt-wt and A30pmentioning
confidence: 99%
“…12 A lack of b-strands N-terminal of position 145 in full-length recPrP-fibrils as demonstrated by H/D exchange, 13 however, indicates that data on truncated PrP-constructs or PrP-fragments are difficult to be extrapolated to infer the full-length PrP-structure. For full-length recPrP(23-231)-fibrils, solid-state NMR studies on selectively 13 CO-labeled samples confirmed an in-register parallel arrangement of b-strands.…”
Section: Introductionmentioning
confidence: 99%